Determinants of Children U5 Mortality due to Malaria in Ghana - Amoako, Martha; Pot??ek, Martin; Verter, Nahanga (European Journal of Sustainable Development, 2023)
Sustainable development cannot be fulfilled without developing an effective health sector to address health-related issues among children, especially in underdeveloped countries like Ghana. Malaria, in particular, has been identified as a significant disease and cause of death among children under five years of age (U5) in Ghana, although it has drastically reduced in recent years. Against this background, this paper attempts to assess some factors that may have determined the development of U5 mortality due to malaria in Ghana using time series data from 2000-2019. The OLS regression results indicate that domestic government health expenditure, clean drinking water and insecticide-treated nets have a negative connection with children U5 mortality due to malaria in the country. The findings also show a weak positive relationship between malaria infection prevalence and U5 mortality from malaria. Contrary to prior expectations, the results reveal a negative relationship between low birth weight, overweight, stunted, and children U5 mortality from malaria infection. The study concludes that addressing malaria cases among children U5 would greatly depend on building and sustaining resource redistribution through strategic policy, reliable funding, and effective health institutions to tackle malaria incidence and deaths among U5 in the country. Keywords: healthcare, health expenditure, ITNs, malaria, potable water, U5 mortality